Adverse reactions for the use of the monoclonal trastuzumab antibody in the treatment of patients with HER2 positive breast cancer - Iago Dilion Lima Cavalcanti; Analúcia Guedes Silveira Cabral; Rosiel José dos Santos
ABSTRACT Objective: Identify the main adverse reactions presented by patients with HER2 positive breast cancer from an outpatient clinic specialized in chemotherapy in the city of Caruaru-PE, after the use of Trastuzumab. Methods: The data were obtained through the analysis of the medical records of the patients attended at the outpatient clinic from January 2015 to December 2016. Results: Twenty-four patients were selected, of whom 12.5% presented cardiotoxicity and 4.16% presented abdominal pain, nausea among other adverse events. Conclusion: Identifying such adverse events makes it possible to better assist the oncological patient and to better adhesion to the treatment. Because they are specific target drugs, few studies are concerned with evaluating these adverse events, which often makes clinical care difficult.